Linking job insecurity and employee creativity: The role of social cyberloafing and talent management - Edi Sugiono (Problems and Perspectives in Management)
This study investigates the relationship between perceived job insecurity and employee creativity, emphasizing the roles of social cyberloafing and talent management practices as mediators and moderators in this relationship. Data were collected from 308 supervisor-subordinate pairs across various sectors in Jakarta, Indonesia. This study utilized Macro Process 4.0 for data analysis, hypotheses testing, and assessing moderation and mediation effects. The findings indicate that job insecurity is positively associated with social cyberloafing and negatively impacts employee creativity. Additionally, social cyberloafing positively influences creativity and mediates the relationship between job insecurity and employee creativity. Furthermore, talent management practices significantly mitigate job insecurity’s negative effects on social cyberloafing and creativity and influence the relationship between social cyberloafing and creativity. This study enhances the understanding of the process model connecting job insecurity and employee creativity in the workplace, highlighting the crucial roles that social cyberloafing and talent management play as mediators and moderators in these relationships.